Physiological and Biochemical Characterization of a Red Escarole Obtained from an Interspecies Crossing - Alessandro Natalini; Giacomo Cocetta; Nazzareno Acciarri; Antonio Ferrante (Agronomy, 2018)
Escarole (Cichorium endivia L.) and radicchio (Cichorium intybus L.) are two important leafy vegetables appreciated by consumers for their sensory attributes, and at the same time, they can be considered a good source of health-promoting secondary metabolites, including polyphenols, flavonoids, and anthocyanins. The aim of this work is the characterization of a new variety of red escarole obtained after a long-term breeding program involving the interspecies crossing between red radicchio and green escarole. Our multidisciplinary approach of investigation allowed us to study the effects of the crossing on several aspects, including the accumulation of phenolic compounds and anthocyanins, the expression pattern of some of the key genes in the phenylpropanoid pathway, and the sensory profiling of the new variety obtained. Given the results, it is possible to conclude that the new variety of red escarole presents traits deriving from both radicchio and escarole. The sensory profile and the preliminary data on yield, suggests that red escarole has interesting characteristics that could be successfully introduced into the market of leafy crops.